Nutritional Composition And Biological Evaluation Of Ficus Hispida Leaves - Abdul Aziz, Siti Hajar (2017)
This study aims investigate the biological potential of Ficus hispida belonging to Family of Moraceae. The cross-section of F. hispida leaf under light microscope showed the presence of xylem, phloem, vascular bundle, collenchyma, unicellular and glandular trichomes, stomata, mesophyll, intercellular space and epidermal layer. The abaxial and adaxial surfaces of the leaf observed via scanning electron microscope overviewed on the polygonal pavement cells, hairy trichome with bulbous base and prickly end, micropapillae, stomata and the paracytic subsidiary cell. Macronutrients of N (2.96±0.02